Joint Trajectories of Spousal Social Support and Depressive Symptoms in Older Age - Stafford, Mai (J Aging Health, 2017)
Objective: We describe changes in depressive symptoms and positive and negative social support from the spouse/partner in a representative sample of older people in England. Method: Men and women aged 50+ (N = 7,171) from the English Longitudinal Study of Ageing reported social support and depressive symptoms (Center for Epidemiologic Studies Depression Scale) on up to five occasions between 2002-2003 and 2010-2011. Parallel process latent growth models estimated their bidirectional associations, adjusted for gender, wealth, education, and limiting illness. Results: In age- and gender-adjusted models, positive spousal support decreased and negative support increased over time, especially among women. Greater increases over time in depressive symptoms were seen in those with lower positive support or higher negative support at baseline. More baseline depressive symptoms predicted greater declines in positive support and greater increases in negative support from the spouse. Discussion: Improving older couple’s relationship quality may help reduce depressive symptoms.